How Do Economic Development Indicators Affect the Poverty Level? Evidence from West Nusa Tenggara - Ali, Muhamad; Agustina, Laila Karina; Pahrudin, Pahrudin (Jurnal Economia, 2024)
AbstractThis study aims to determine the effect of GRDP, HDI, Economic Growth, and Unemployment Rate on poverty levels in West Nusa Tenggara Province. The method used the Random Effect Model as the selected model through a series of model selection tests and classical assumption tests. Regression results using the selected model show that of the four variables that cause poverty rates, only the HDI variable negatively and significantly affects poverty rates. Meanwhile, the other three variables (GRDP, economic growth, and unemployment rate) do not significantly affect poverty. The result suggests that the West Nusa Tenggara government should increase the HDI through stimulus programs in terms of education and health to provide more human resources, create more jobs for the lower and middle class to overcome unemployment and reduce poverty level, and expand the scope of GRDP and development in the economic structure sector to reduce the poverty level.  Keywords:GRDP, HDI, panel data, random effects models